Possibilidades e desafios na contextualização dos conteúdos de física do ensino médio - Nogueira, Carolina de Luca Menezes (2019)
This work has as presupposition that the teaching of physics can train students to prepare them for work and citizenship, since it allows to relate the contents and physical phenomena with the reality of the students, making them critical and responsible so that they can make decisions scientifically and technologically. Thus, characterizing the contextualization of teaching as a possibility to lead the student to a citizenship education through teaching physics concepts linked to their experience and being thought as a pedagogical resource or as a guiding principle of the teaching and learning process we elaborated an experimental contextualized research activity and a stimulated interview in order to analyze the relationship that students establish with the contextualization of contents from an investigative activity and how they perceive the aspects of contextualization within the discipline. The activity was applied to students of the 1st year of high school of a public school in the city of São Carlos. The research has a qualitative methodological character and, for data analysis, significant parts of Content Analysis were used, in which categories were created that best represented the students' relationship with the contextualization during the activity. We realize that curricular content has a difficulty in bringing school knowledge closer to students 'curiosities and that there is a challenge in physics classes to identify students' needs and curiosities in order to articulate them with curriculum content.